A comparison of two compression algorithms and the detection of caries - Janhom A. (2014)
Objectives: To assess the effect of two compression algorithms (JPEG and wavelet) on the detection of approximal caries. Methods: Fifteen bitewing radiographs were generated using 100 posterior teeth mounted in blocks. The images were produced on conventional films (Ektaspeed Plus) and scanned at 300 d.p.i. Digital images were then compressed 9:1 with JPEG and wavelet methods. Nine observers detected the presence and depth of approximal caries recorded on a 5-point confidence scale and a 4-point depth scale from images viewed in random order. Histological examination provided the true depth of the lesions. Data were analysed by means of ANOVA. The null hypothesis was that there is no significant difference between the two compression algorithms and the original uncompressed images. Results: JPEG performed significantly worse than the original and the wavelet algorithm (P<0.001) for the detection of dentinal lesions. However, no significant differences were found for the detection of sound surfaces, enamel lesions, and lesions up to the DEJ between JPEG-compressed images and each of the other two modalities. There was also no significant difference between the wavelet-compressed images and the original for all lesion depths. Conclusions: At a compression ratio of 9:1, there were no significant differences among the original images, JPEG and wavelet compressed images for the detection of enamel caries. JPEG-compressed images performed inferiorly to the original and wavelet-compressed images for the detection of dentinal lesions. Wavelet compression is a better choice than JPEG at the compression ratio investigated in this study.